Increased brain gyrification and cortical thinning in winter-born patients with schizophrenia spectrum - Torigoe, Misako; Takahashi, Tsutomu; Takayanagi, Yoichiro; Sasabayahi, Daiki; Kobayashi, Haruko; Sakamoto, Kazumi; Yuasa, Yusuke; Tsujii, Noa; Noguchi, Kyo; Suzuki, Michio (Frontiers in Psychiatry, 2024)
The findings of epidemiological studies suggest that a relationship exists between the risk of schizophrenia and winter births in the Northern Hemisphere, which may affect the process of fetal neurodevelopment. However, it remains unclear whether birth seasons are associated with the brain morphological characteristics of patients within the schizophrenia spectrum.The present magnetic resonance imaging study using FreeSurfer software examined the effects of birth seasons (i.e., summer-born vs. winter-born) on the comprehensive brain surface characteristics of 101 patients with schizophrenia ( 48summer-and 53 winter-born), 46 with schizotypal disorder (20 summer-and 26 winterborn), and 76 healthy control subjects (28 summer-and 48 winter-born).In comparisons with summer-born patients, winter-born patients, particularly those with schizophrenia, showed significantly increased gyrification mainly in the left lateral occipital and inferior temporal regions and right fronto-parietal region as well as cortical thinning in the right superior frontal region. Birth seasons did not significantly affect the local gyrification index or cortical thickness in healthy controls.Discussion: The present whole-brain surface-based analysis demonstrated that brain morphological characteristics reported in the schizophrenia spectrum were more pronounced in winter-born patients than in summer-born patients, suggesting the contribution of early neurodevelopmental factors associated with birth seasons to the pathophysiology of the schizophrenia spectrum.